DOES FINANCIAL PERFORMANCE MEDIATE THE RELATIONSHIP BETWEEN ESG PERFORMANCE AND FIRM VALUE? - Bela Nabila; Titi Dewi Warninda (Program Studi Akuntansi Institut Bisnis dan Informatika (IBI) Kosgoro 1957, 2026)
This study explores how ESG (Environmental, Social, Governance) performance influences firm valuation, using financial performance in a mediating capacity. Here, ESG acts as the independent variable, while Tobin's Q proxies for the dependent variable of firm value. Financial performance as mediator is gauged by Return on Assets (ROA) and Return on Equity (ROE). Data covers 49 firms from the IDX ESG Leaders Index over the 2020-2023 period. Panel data regression is employed to examine the direct relationship, followed by mediation analysis to assess the mediating effect and the Sobel test to assess the significance of indirect effects. The results indicate that ESG performance exerts no significant impact on firm value, nor does it affect ROA or ROE. Conversely, both ROA and ROE demonstrate a significant positive influence on firm value. Nevertheless, financial performance measured by ROA and ROE fails to mediate the link between ESG performance and firm value. One possible explanation for this result is that strong ESG practices do not automatically translate into short-term gains in a company’s profitability. In the observed period, ESG initiatives are sometimes perceived as additional costs that may impose a financial burden on the firm, thereby limiting their ability to improve short-term financial performance and potentially reducing shareholder wealth.